Optimized local therapy for locally advanced non-small cell lung cancer - Billiet, Charlotte; De Ruysscher, Dirk (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
The optimal local treatment of patients with stage IIIA non-small cell lung cancer (NSCLC) is one of the most controversial areas. Specifically, the selection of patients for multimodality therapy and the sequencing of therapies remain unclear. As patients with stage IIIA disease consist of a heterogeneous group with various extents of their lung tumor, nodal status and co-morbidities, different approaches have been adopted.